## 65 Reputation

4 years, 343 days

## @acer I was able to plot one of the...

@acer I was able to plot one of the graphs but i dont know how to do both together. plots[animate](plot, [cos(x-2*a), x = 0 .. 10], A = 1 .. 10)

## solve({y = (c*z^2 + b*z + a)/(f*z^2 + e*...

solve({y = (c*z^2 + b*z + a)/(f*z^2 + e*z + d)}, {z});
/         1       /          /        2    2  2
{ z = ------------ \e y - b + \-4 d f y  + e  y  + 4 a f y
\    2 (-f y + c)

2\      \\    /
- 2 b e y + 4 c d y - 4 a c + b /^(1/2)/ }, { z = -
/    \

1       /       /        2    2  2
------------ \-e y + \-4 d f y  + e  y  + 4 a f y - 2 b e y
2 (-f y + c)

2\          \\
+ 4 c d y - 4 a c + b /^(1/2) + b/ }
/
f := y -> [z = (e*y - b + sqrt(-4*d*f*y^2 + e^2*y^2 + 4*a*f*y - 2*b*e*y + 4*c*d*y - 4*a*c + b^2))/(-2*f*y + 2*c), z = -(-e*y + sqrt(-4*d*f*y^2 + e^2*y^2 + 4*a*f*y - 2*b*e*y + 4*c*d*y - 4*a*c + b^2) + b)/(-2*f*y + 2*c)];
f := proc (y) options operator, arrow; [z = (e*y-b+sqrt(-4*d*f*y\

^2+e^2*y^2+4*a*f*y-2*b*e*y+4*c*d*y-4*a*c+b^2))/(-2*f*y+2*c),

z = -(-e*y+sqrt(-4*d*f*y^2+e^2*y^2+4*a*f*y-2*b*e*y+4*c*d*y-4*\

a*c+b^2)+b)/(-2*f*y+2*c)] end proc
g := z -> (a + b*z + c*z^2)/(d + e*z + f*z^2);
g := proc (z) options operator, arrow; (a+b*z+c*z^2)/(d+e*z+f*z^\

2) end proc
r := (g@f)(y);
/      [         1       /          /        2    2  2
r := |a + b [z = ------------ \e y - b + \-4 d f y  + e  y
\      [    -2 f y + 2 c

2\      \
+ 4 a f y - 2 b e y + 4 c d y - 4 a c + b /^(1/2)/, z = -

1       /       /        2    2  2
------------ \-e y + \-4 d f y  + e  y  + 4 a f y - 2 b e y
-2 f y + 2 c

2\          \]     [         1       /
+ 4 c d y - 4 a c + b /^(1/2) + b/] + c [z = ------------ \e y
]     [    -2 f y + 2 c

/        2    2  2
- b + \-4 d f y  + e  y  + 4 a f y - 2 b e y + 4 c d y - 4 a c

2\      \             1       /       /        2    2  2
+ b /^(1/2)/, z = - ------------ \-e y + \-4 d f y  + e  y
-2 f y + 2 c

2\          \]  \//
+ 4 a f y - 2 b e y + 4 c d y - 4 a c + b /^(1/2) + b/]^2| |d + e
]  / \

[         1       /          /        2    2  2
[z = ------------ \e y - b + \-4 d f y  + e  y  + 4 a f y
[    -2 f y + 2 c

2\      \             1       /
- 2 b e y + 4 c d y - 4 a c + b /^(1/2)/, z = - ------------ \
-2 f y + 2 c
/        2    2  2
-e y + \-4 d f y  + e  y  + 4 a f y - 2 b e y + 4 c d y - 4 a c

2\          \]     [         1       /          /        2
+ b /^(1/2) + b/] + f [z = ------------ \e y - b + \-4 d f y
]     [    -2 f y + 2 c

2  2                                          2\      \
+ e  y  + 4 a f y - 2 b e y + 4 c d y - 4 a c + b /^(1/2)/, z =

1       /       /        2    2  2
- ------------ \-e y + \-4 d f y  + e  y  + 4 a f y - 2 b e y
-2 f y + 2 c

2\          \]  \
+ 4 c d y - 4 a c + b /^(1/2) + b/]^2|
]  /
simplify(r, eqns);
/      [         1       /          //          2\  2
|a + b [z = ------------ \e y - b + \\-4 d f + e / y
\      [    -2 f y + 2 c

2\      \
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/, z = -

1       /           //          2\  2
------------ \-e y + b + \\-4 d f + e / y
-2 f y + 2 c

2\      \]     [
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/] + c [z =
]     [

1       /          //          2\  2
------------ \e y - b + \\-4 d f + e / y
-2 f y + 2 c

2\      \
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/, z = -

1       /           //          2\  2
------------ \-e y + b + \\-4 d f + e / y
-2 f y + 2 c

2\      \]  \//      [
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/]^2| |d + e [z =
]  / \      [

1       /          //          2\  2
------------ \e y - b + \\-4 d f + e / y
-2 f y + 2 c

2\      \
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/, z = -

1       /           //          2\  2
------------ \-e y + b + \\-4 d f + e / y
-2 f y + 2 c

2\      \]     [
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/] + f [z =
]     [

1       /          //          2\  2
------------ \e y - b + \\-4 d f + e / y
-2 f y + 2 c

2\      \
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/, z = -

1       /           //          2\  2
------------ \-e y + b + \\-4 d f + e / y
-2 f y + 2 c

2\      \]  \
+ (4 a f - 2 b e + 4 c d) y - 4 a c + b /^(1/2)/]^2|
]  /

## my work that I have done so far...

this is my graphing of the implicit

## @Kitonum its 12^(6^5)...

@Kitonum its 12^(6^5)

 Page 1 of 1
﻿